Almanac 2013: Novel non-coronary cardiac interventions. Issue 18 (30th July 2013) - Meier, Pascal; Franzen, Olaf; Lansky, Alexandra J
Abstract : Recent innovations in interventional cardiology have dramatically expanded the therapeutic options for patients with cardiac conditions. Interventional cardiology is no longer limited to the treatment of coronary artery disease but allows also treatment of valvular disease, stroke prevention, hypertension, etc. One of the most important new treatment options is the percutaneous treatment for aortic valve stenosis (transcatheter aortic valve implantation), since aortic valve disease is a rather common problem in elderly patients, with many of them at high risk for surgery. Similarly, mitral regurgitation is often associated with comorbidities which make surgery high risk. The MitraClip is a promising percutaneous alternative to surgical valve repair or replacement. Other procedures discussed in this review are the percutaneous left atrial appendage closure as a non-pharmacologic therapy to prevent strokes, and renal denervation for resistant hypertension. This review explains the basic principles of these procedures, the most important clinical evidence, and also provides additional recent clinical data on each of these them.